The sounding cosmos a study in the spiritualism of Kandinsky and the genesis of abstract painting - Ringbom, Sixten 1935-1992 (Bokförlaget Stolpe, 2022)
The Sounding Cosmos kommer nu for forsta gangen i ny utgava och med ny form som ger utrymme at Kandinskys fargstarka malningar. Ursprungs texten har kompletterats med ett forord av Daniel Birnbaum och Julia Voss. Boken utkommer endast pa engelska
Orginally published in 1970 by Ábo Akademi. No substantial text changes have been made for this edition.
Keywords: Kandinsky, Wassily -- 1866-1944; Spiritualismus